2014
DOI: 10.1097/ncc.0b013e31828941bb
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience in Illness Model, Part 1

Abstract: Background Resilience is a positive health outcome identified by the Committee on Future Direction for Behavioral and Social Sciences as a research priority for the National Institutes of Health. The Resilience in Illness Model (RIM) was developed from a series of qualitative and quantitative studies, to increase understanding of how positive health protective factors (i.e. social integration, family environment, courageous coping and derived meaning) may influence resilience outcomes. The RIM also includes tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 41 publications
4
61
0
Order By: Relevance
“…Our result indicated positive correlation of resilience with hope, and it is in accordance with previous study findings [17, 40]. A longitudinal study conducted by Ho et al [17] found hopefulness may predict resilience after hereditary colorectal cancer genetic testing in Hong Kong Chinese.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our result indicated positive correlation of resilience with hope, and it is in accordance with previous study findings [17, 40]. A longitudinal study conducted by Ho et al [17] found hopefulness may predict resilience after hereditary colorectal cancer genetic testing in Hong Kong Chinese.…”
Section: Discussionsupporting
confidence: 92%
“…A longitudinal study conducted by Ho et al [17] found hopefulness may predict resilience after hereditary colorectal cancer genetic testing in Hong Kong Chinese. Solano [41] and Haase [40] respectively carried out a cross-sectional study and found positive correlation of resilience with hope among metastatic colorectal cancer patients and adolescent/young adults with cancer. Hope is an inner power energized in the face of adversity, which could enable patients to establish positive and realistic goals, and mobilize resources to positively manage the physical and psychological challenges.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs can have a profound impact on how patients cope with their diagnosis. A theoretical model that demonstrates the potential impact that HCPs have on AYA patients is the Resilience in Illness Model (formerly called the Adolescent Resilience Model) (Haase, 2004; Haase, Kintner, Monahan, & Robb, 2014). In this model, the nature of the AYA–HCP relationship is a protective factor and considered to have an influence on moving AYAs away from the use to defensive coping strategies and towards courageous coping strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators evaluate the associations between resilience and coping in a different way by proposing that certain coping strategies contribute to greater resilience. 50 Longitudinal research is needed to shed light on the causal ordering. Second, the acceptance rate of 25.6% is relatively low and may have resulted in a biased sample.…”
Section: Discussionmentioning
confidence: 99%